An open-label trial of abatacept (CTLA4-IG) in non-severe relapsing granulomatosis with polyangiitis (Wegener's). Issue 7 (9th December 2013) - Langford, Carol A; Monach, Paul A; Specks, Ulrich; Seo, Philip; Cuthbertson, David; McAlear, Carol A; Ytterberg, Steven R; Hoffman, Gary S; Krischer, Jeffrey P; Merkel, Peter A; ,
Abstract : Objectives: To determine the safety and efficacy of abatacept in non-severe relapsing granulomatosis with polyangiitis (Wegener's)(GPA). Methods: An open-label trial of intravenous abatacept was conducted in 20 patients with non-severe relapsing GPA. Prednisone up to 30 mg daily was permitted within the first 2 months, and patients on methotrexate, azathioprine, or mycophenolate mofetil continued these agents. Patients remained on study until common closing or early termination. Results: Of the 20 patients, 18 (90%) had disease improvement, 16 (80%) achieved remission (BVAS/WG=0) at a median of 1.9 months, and 14 (70%) reached common closing. Six patients (30%) met criteria for early termination due to increased disease activity; 3 of 6 achieved remission and relapsed at a median of 8.6 months. The median duration of remission before common closing was 14.4 months, with the median duration of time on study for all patients being 12.3 months (range 2–35 months). Eleven of the 15 (73%) patients on prednisone reached 0 mg. Nine severe adverse events occurred in 7 patients, including 7 infections that were successfully treated. Conclusions: In this study of patients with non-severe relapsing GPA, abatacept was well tolerated and was associated with a high frequency of disease remission and prednisone discontinuation.